A Coupled Approach for Fluid Dynamic Problems Using the PDE Framework Peano (Communications in Computational Physics, 2012)
We couple different flow models, i.e. a finite element solver for the Navier-Stokes equations and a Lattice Boltzmann automaton, using the framework Peano as acommon base. The new coupling strategy between the meso- and macroscopic solveris presented and validated in a 2D channel flow scenario. The results are in goodagreement with theory and results obtained in similar works by Latt et al. In addition,the test scenarios show an improved stability of the coupled method compared to pureLattice Boltzmann simulations.